2020
DOI: 10.1111/jonm.13171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses' perspectives on discharge practice changes from participating in a translational research study

Abstract: Aim To describe clinical nurses' experiences with practice change associated with participation in a multi‐site nursing translational research study implementing new protocols for hospital discharge readiness assessment. Background Nurses' participation in translational research studies provides an opportunity to evaluate how implementation of new nursing interventions affects care processes within a local context. These insights can provide information that leads to successful adoption and sustainability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The alert cards were paper‐based, and in one study some patients took a photo of the paper‐based card on their phones (Kapil et al, 2016; Keng et al, 2015). The final type 1 intervention was READI, where patients used a paper‐based assessment to report their discharge readiness 4 h prior to discharge; and nurses were provided with instructions on how to respond to patient scores (Bobay et al, 2021; Weiss et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The alert cards were paper‐based, and in one study some patients took a photo of the paper‐based card on their phones (Kapil et al, 2016; Keng et al, 2015). The final type 1 intervention was READI, where patients used a paper‐based assessment to report their discharge readiness 4 h prior to discharge; and nurses were provided with instructions on how to respond to patient scores (Bobay et al, 2021; Weiss et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The implementation process was evaluated by Costa et al [ 106 ]. As part of the implementation study, nurses were interviewed in focus groups and their involvement in the discharge readiness assessment resulted in improved and earlier awareness of patients' discharge needs and greater patient/family involvement [ 107 ]. This result indicates that discharge readiness assessed from patients and nurses' points of view can be useful in avoiding negative patient outcomes and reinforcing the RHDS as a useful instrument for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nurses reported that a benefit of implementing the structured discharge readiness assessment was improved contribution to and communication with the care team in discharge planning and decision-making. 43 Fourth, we may not have accounted adequately for factors that increase the likelihood of HHC referral; for example, we included an indicator for medical or surgical case type but did not have data on the need for wound care, a common reason for HHC referral. Lastly, our study sampled only patients with Medicare insurance receiving care in Magnet facilities, limiting generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while the READI study protocol included instructions to the discharging nurse to use the assessment in planning discharge care, no information was collected on communication and use within the multidisciplinary team process. However, the nurses reported that a benefit of implementing the structured discharge readiness assessment was improved contribution to and communication with the care team in discharge planning and decision-making 43 . Fourth, we may not have accounted adequately for factors that increase the likelihood of HHC referral; for example, we included an indicator for medical or surgical case type but did not have data on the need for wound care, a common reason for HHC referral.…”
Section: Discussionmentioning
confidence: 99%